Implementation of Good Governance Principles and Their Role on Performance in Village Owned Enterprises (BUMDes) - Hanafi Hanafi; Retno Kusumastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research in the form of community service that the author conducted has the aim of analyzing how the implementation of Transparency, responsiveness, professionalism, rule of law vision strategic has been applied to contribute to the performance of Village Owned Enterprises (BUMD). The survey was conducted using a descriptive and exploratory qualitative approach. The research was conducted using a descriptive exploratory qualitative approach. The data were obtained through interviews with competence to explain the state of the South Maja Bumdes. The purpose of this research is to find that governance practices with the principles of transparency, responsiveness, professionalism, rule of law, and vision strategies can hinder the performance of Village Owned Enterprises (BUMDes). The research to be carried out is a qualitative descriptive exploratory research. The author obtained data from informants through interviews, the informants used were competent parties and had knowledge about the activities of Bumdes in Maja Selatan Village. The results survey this will be used as input and evaluation material for improving the performance of the South Maja Bumdes, Maja District, Majalengka Regency. The results of research conducted by Kurniasih (2014) explained that the poor performance of Bumdes was partly due to the inability of managers to create efficiency, effectiveness, and weak responsiveness. This condition can be seen from the suboptimal local village resources in the management of the Bumdes, as well as the weak participation of the community in the management of the Bumdes. Sofyani, et al. (2019) provides an explanation that the determining factors in improving the performance of Bumdes are the involvement and enthusiasm of the community, the competence of Bumdes managers, education and training for Bumdes managers, honest behavior, good teamwork, good communication, kind, transparent and responsible.